因式分解:(a+b)^2 - 4a^2 =
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 05:09:11
因式分解:(a+b)^2-4a^2=因式分解:(a+b)^2-4a^2=因式分解:(a+b)^2-4a^2=(a+b)^2-4a^2=(a+b+2a)(a+b-2a)=(3a+b)(-a+b)(a+b
因式分解:(a+b)^2 - 4a^2 =
因式分解:(a+b)^2 - 4a^2 =
因式分解:(a+b)^2 - 4a^2 =
(a+b)^2 - 4a^2
=(a+b+2a)(a+b-2a)
=(3a+b)(-a+b)
(a+b)^2 - 4a^2 =(a+b+2a)(a+b-2a)=(3a+b)(b-a)
(a+b)^2 - 4a^2
原式=(a+b+2a)(a+b-2a)
=(3a+b)(-a+b)
回答完毕
祝你答题愉快
有什么不会的可以问我啊
(*^__^*) 嘻嘻……
(a+b)²-4a²
=[(a+b)-2a][(a+b)+2a]
=(a+b-2a)(a+b+2a)
=(b-a)(3a+b)
因式分解4a(a-b)+b^2
4(a+b)^2-(a+b)因式分解
因式分解:4a(a-b)+b^2
因式分解:4a(a+b)+b^2
因式分解a^4-a^2b^2
因式分解:a^4-(5a+b)^2
因式分解:a×a-4b×b-2a+4b
因式分解4a^2b-4b
a^2b-4b^3因式分解
因式分解 2(a+b)2-4a(a+b)
因式分解(b+2a)(b-2a)+4a-1
4(a+b)-2a(a+b)因式分解
因式分解4a^2(a-b)+(b-a)
a^3b+2a^2b+ab因式分解因式分解
a^2+4ab+b^2因式分解
4ab-a^2-b^2 因式分解
a^2-4b^2=因式分解
因式分解:4a^2-(b-c)^2